Learning and Doing Policy Analysis in Education Examining Diverse Approaches to Increasing Educational Access - Tatto, Maria Teresa; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This book originated in a policy analysis class at Michigan State University taught during 2010. Using Professor Tatto$1 (Bs unique approach to teaching policy analysis, the professor and students agreed to construct a class that represented a reflective and grounded experience in the policy analysis of a current and relevant issue with global ramifications; we began exploring policies that were developed at the global level and that were implemented locally. We investigated the surge of globally developed standards and regulations in an effort to improve education. Our goal was to learn cross-nationally about policies that seek to reform curriculum and instruction under efficiency and global competitiveness arguments, such as Education for All (EFA) and its USA cousin No Child Left Behind (NCLB). We knew our work would be bounded by the time available in a one-semester class, and by resource constraints. We did exploratory inquiry supported by literature reviews, reports on rigorous research studies, and in one case an exploratory case study. The policies we chose to explore, such as EFA and NCLB, offered us the opportunity to examine current reform tendencies that are intended to provide access to quality education for all children, the preparation of teachers to support diverse populations, the organization of schools to accommodate these children in response to vague policy mandates, and power issues affecting the different constituencies and stakeholders. The effects of these and other policies were difficult to track because research is scant and decisions are frequently made based on ideology or political persuasion. Our purpose was to explore the critical issues that originated such policies, and to search for documented evidence regarding policy implementation and effectiveness. We investigated the factors that seemed to interfere with successful implementation, from conceptual, theoretical, and methodological perspectives. In this class we learned that there are not ready-set frameworks for policy analysis, but rather that these have to be constructed according to the issues that emerge as policies are conceptualized and implemented to fit local contexts and needs. The book pays particular attention to the contexts of policy, including the evolving conceptualization of global and local systems of governance, knowledge regimes, and policy spaces. The book is designed for faculty and doctoral students in education who are interested in understanding diverse frameworks for policy analysis, and for those in the general public who are interested in the policies we analyze here.s
Keywords: Education; Education; Education (general).